THE FORMATION AND DEVELOPMENT OF THE BANKING SYSTEM in Kyrgyz Republic (Journal of actual problems of jurisprudence, 2019)
Becoming and development of bank system is happen in difficult conditions witch connecting with unstable in economy whereabsence native experiment of construction and legal regulation of credit-bank system in conditions of market economy. In modernmarket economy bank system has big mean, thanks to its connection with all sector of economy and because of its too big andintense, mainly depend on possibility development its sector. Basic constituent of economical reform witch making in KyrgyzRepublic is reform of basic branch of market economy – reform bank system.